The influence of psychological ownership on the association between satisfaction with work-family balance and intention to stay among nurses in South-eastern Nigeria public hospitals - Ebele, E. Nnadozie; Obinna O. Ike; Ngozi U. Chuke; Ifeanyichukwu C. Eze (Elsevier, 2022)
The study investigated the influence of psychological ownership on the association between satisfaction with work-family balance and intention to stay in the profession in South-Eastern Nigerian public hospitals. An exploratory research design was adopted for a study that was conducted among 389 nurses recruited from public hospitals in South-eastern Nigeria (females: 373 (96 %); males: 16(4 %); mean age: 37.40 years; SD = 6.33). Participants completed self-report measures of satisfaction with work-family balance, psychological ownership, and intention to stay. Regression analyses showed that work-family balance and psychological ownership positively correlated with nurses' intention to stay. Psychological ownership also moderated the relationship between satisfaction with work-family balance and intention to stay. These findings indicated that psychological ownership and satisfaction with work-family balance are necessary preconditions for striking a balance between job demands and employees' responsibilities to encourage intention to stay and improve commitment and productivity. Thus, the current findings help hospital managements comprehend and appreciate the critical roles of psychological ownership and satisfaction with work-family balance in enhancing nurses' intention to stay.